Does Intraoperative Ulinastatin Improve Postoperative Clinical Outcomes in Patients Undergoing Cardiac Surgery: A Meta-Analysis of Randomized Controlled Trials. (9th March 2014) - He, Qiu-Lan; Zhong, Fei; Ye, Fang; Wei, Ming; Liu, Wei-Feng; Li, Mei-Na; Li, Qiao-Bo; Huang, Wen-Qi; Sun, Lai-Bao; Shu, Hai-Hua
Abstract : Introduction . The systematic meta-analysis of randomized controlled trials (RCTs) evaluated the effects of intraoperative ulinastatin on early-postoperative recovery in patients undergoing cardiac surgery. Methods. RCTs comparing intraoperative ulinastatin with placebo in cardiac surgery were searched through PubMed, Cochrane databases, Medline, SinoMed, and the China National Knowledge Infrastructure (1966 to May 20th, 2013). The primary endpoints included hospital mortality, postoperative complication rate, length of stay in intensive care unit, and extubation time. The physiological and biochemical parameters illustrating postoperative cardiac and pulmonary function as well as inflammation response were considered as secondary endpoints. Results. Fifteen RCTs (509 patients) met the inclusion criteria. Ulinastatin did not affect hospital mortality, postoperative complication rate, or ICU length of stay but reduced extubation time. Ulinastatin also increased the oxygenation index on postoperative day 1 and reduced the plasma level of cardiac troponin-I. Additionally, ulinastatin inhibited the increased level of tumor necrosis factor-alpha, polymorphonuclear neutrophil elastase, interleukin-6, and interleukin-8 associated with cardiac surgery. Conclusion. Ulinastatin may be of value for the inhibition of postoperative increased inflammatory agents and most likely provided pulmonary protective effects in cardiac surgery. However, larger adequately powered RCTs are required to define the clinical effect of ulinastatin on postoperative outcomes in cardiac surgery.